ANALISIS PERAN PEMERINTAH DESA DALAM MENINGKATKAN KUALITAS KELEMBAGAAN BADAN USAHA MILIK DESA (BUMDes Desa Kalongan Kecamatan Ungaran Timur Kabupaten Semarang) - Nabilla, Dhea -; -, Kushandajani - (Journal of Politic and Government Studies, 2025)
This study aims to analyze the role of the village government in improving the institutional quality of Village-Owned Enterprises (BUMDes) in Kalongan Village, Ungaran Timur District, and to identify the application of good governance principles. The phenomenon indicates that although there was an increase in the capital score of BUMDes in 2022, the scores for institutional quality, business, and administration experienced a significant decline during the 2019–2022 period. This condition demands attention to more effective and sustainable management strategies. The study employs a qualitative method with a descriptive approach. Data were collected through observation, in-depth interviews with the village head, village officials, and BUMDes managers, as well as document analysis. The data analysis process was conducted inductively to obtain a comprehensive understanding of the research problems and to systematically address the research questions. The findings reveal that the application of good governance principles, including transparency, accountability, and community participation, is a key factor in improving the institutional quality of BUMDes. The role of the village government as a coordinator, stimulator, and facilitator significantly contributes to optimizing the functions of BUMDes. The village government also plays a critical role in creating a supportive environment through policies and development programs based on local needs. This study concludes that improving the institutional quality of BUMDes requires governance based on good governance principles with active support from the village government and the community. This study provides practical implications for village governments in formulating strategic policies to strengthen the role of BUMDes as drivers of the village economy